KAWASAN EKONOMI KHUSUS DAN POTENSI PARIWISATA PROVINSI KEPULAUAN BANGKA BELITUNG (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2018)
Special Economic Zone is a program that supports the acceleration of Indonesia's economic development and tourism into one of the sectors included in the Special Economic Zone. Bangka Belitung Islands Province is a beautiful province and rich in natural resources to serve as a tourism destination. With good planning and management of the Province of Bangka Belitung Islands can be a tourism destination that is taken into account by tourists in the country and abroad.